Development of personalised learning model for dental students through machine learning application - Shoaib, Lily Azura; Sazali, Amin Hakim; Idris, Norisma; Safii, Syarida Hasnur; Hussin, Ruhaya (Universiti Putra Malaysia, 2022)
Personalisation of learning through integration of advanced technologies aim to understand the dental students’ learning styles and strategies. Modified index of Learning Styles based on index of learning style and Felder Solomon Learning Model was used to identify students’ learning style. A machine learning approach was then applied to automate classification of student’s learning style. Through arule-based technique, a recommendation for student's best learning strategies was carried out.